Artificial graphite, method for manufacturing the same, and secondary battery and electric device including the artificial graphite
Patent Information
- Application Number
- CN202180091185.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-24
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-12-24
AI Technical Summary
[0025]本申请所提供的二次电池中,负极活性材料包括人造石墨,该人造石墨包括二次颗粒,且满足:A≥0.5,其中,所述A为所述人造石墨在2t压力下的粉体压实密度与所述人造石墨的体积分布粒径Dv1的比值。本申请提供的人造石墨颗粒圆润,可以显著提升颗粒与颗粒之间的结合力,在二次电池的循环过程中,作为负极活性材料的人造石墨颗粒与颗粒之间的较高的结合力能够有效保持颗粒与颗粒的接触,降低极片厚度增长,从而可以显著降低极片膨胀,进而能够使含有该人造石墨的二次电池在循环过程中的体积膨胀明显降低。二次电池在循环过程中的体积膨胀较小,有利于使其保持较高的体积能量密度;较低的体积膨胀还能降低二次电池的电芯内应力,减小电芯在内应力作用下产生的变形,使二次电池的安全性能也得到有效改善。因此,本申请所涉及的人造石墨可以提高二次电池的安全性能和能量密度。此外,低体积膨胀的二次电池能在循环过程中保持适于电解液浸润的内部结构,使得电解液能够充分浸润于电芯中,增加锂离子传输通道,从而提高二次电池的循环性能。同时,较低的极片膨胀还有利于避免电芯短路的风险,进而可以提高二次电池的安全性能。本申请的用电装置包括本申请提供的二次电池,因而至少具有与所述二次电池相同的优势。
Smart Images

Figure CN116745956B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, and in particular to an artificial graphite, a method for preparing the same, and a secondary battery and electrical device containing the artificial graphite. Background Technology
[0002] Secondary batteries are widely used due to their outstanding characteristics such as high energy density, no pollution, and long service life.
[0003] However, in secondary batteries, continuous charging and discharging causes volume changes in the negative electrode active material during lithium insertion / extraction, such as volume expansion during cycling. This increases the battery's internal stress, thus affecting its lifespan and safety performance. Recently, with the rapid popularization of new energy vehicles, the market demands increasingly higher lifespan and safety performance from power-type secondary batteries. Therefore, to enhance the market competitiveness of new energy vehicles, it is necessary to provide a new technology that can reduce the volume expansion of secondary batteries. Summary of the Invention
[0004] This application was made in view of the above-mentioned problems, and its object is to provide a low-expansion artificial graphite with high specific capacity, a method for preparing the same, and a negative electrode sheet prepared from the artificial graphite as a negative electrode active material. Furthermore, this application also aims to provide a secondary battery with low volume expansion and high energy density during cycling, and an electrical device comprising the secondary battery.
[0005] To achieve the above objectives, a first aspect of this application provides an artificial graphite comprising secondary particles, satisfying: A ≥ 0.5; wherein, A is the compacted density of the artificial graphite powder under a pressure of 2t (in g / cm³). 3 Its volume distribution and particle size D v The ratio of 1 (unit: μm).
[0006] In some embodiments, the artificial graphite satisfies: 0.50≤A≤1.40, optionally 0.70≤A≤1.30, and further optionally 0.70≤A≤1.00.
[0007] In some embodiments, the artificial graphite may be secondary particles.
[0008] In some embodiments, the compacted density of the artificial graphite powder under a pressure of 2t can be 1.60 g / cm³. 3 -1.95g / cm 3 1.70 g / cm³ is an optional value. 3 -1.90g / cm 3 .
[0009] In some embodiments, the volume distribution particle size D of the artificial graphite v 1 can be 1.5μm-3.5μm, can be selected from 1.8μm-3.2μm, and can be further selected from 2.0μm-3.2μm.
[0010] In some embodiments, the volume distribution particle size D of the artificial graphite v 50 can be 10.0μm-20.0μm, and can be selected from 12.0μm-18.0μm.
[0011] In some embodiments, the specific capacity of the artificial graphite is 350 mAh / g or more, and optionally 352 mAh / g or more.
[0012] A second aspect of the present invention provides a method for preparing artificial graphite, comprising the following steps:
[0013] S1: The raw materials are crushed, graded, and shaped to obtain the precursor;
[0014] S2: Granulate the precursor obtained in step S1 to obtain intermediate 1;
[0015] S3: The intermediate 1 obtained in step S2 is graphitized at a temperature of 2700℃-3200℃ to obtain intermediate 2;
[0016] S4: The intermediate 2 obtained in step S3 is mechanically processed in a mechanical fusion machine to obtain artificial graphite;
[0017] The artificial graphite comprises secondary particles and satisfies: A ≥ 0.5, where A is the compacted density of the artificial graphite powder under 2t pressure and the volume distribution particle size D of the artificial graphite. v The ratio of 1.
[0018] In some embodiments, during the mechanical processing in step S4, the rotation speed of the mechanical fusion machine can be 600rpm-1400rpm, or optionally 800rpm-1200rpm.
[0019] In some embodiments, the processing time for the mechanical treatment in step S4 can be 5 min to 30 min, or optionally 5 min to 25 min.
[0020] In some embodiments, a binder may be added during the granulation process in step S2, and the amount of binder added may be 5%-15% of the weight of the precursor used for granulation in step S2; optionally, the binder may include one or more of coal tar, asphalt, epoxy resin, and phenolic resin.
[0021] In some embodiments, the raw materials in step S1 may include one or more of petroleum coke, calcined petroleum coke, needle coke, calcined needle coke, pitch coke, and metallurgical coke; optionally, the raw materials may include one or more of petroleum coke, needle coke, and calcined needle coke.
[0022] A third aspect of this application provides a secondary battery comprising a negative electrode sheet, the negative electrode sheet comprising a negative electrode active material, the negative electrode active material comprising artificial graphite provided in the first aspect of this application or comprising artificial graphite prepared according to the method provided in the second aspect of this application.
[0023] A fourth aspect of this application provides an electrical device that includes a secondary battery as described in the third aspect of this application.
[0024] Beneficial effects
[0025] In the secondary battery provided in this application, the negative electrode active material includes artificial graphite, which comprises secondary particles and satisfies: A ≥ 0.5, where A is the compacted density of the artificial graphite powder under a pressure of 2t and the volume distribution particle size D of the artificial graphite. v The ratio of 1 to 1. The rounded artificial graphite particles provided in this application can significantly improve the bonding force between particles. During the cycling process of the secondary battery, the high bonding force between the artificial graphite particles, which serve as the negative electrode active material, can effectively maintain the contact between particles, reduce the increase in electrode thickness, and thus significantly reduce electrode expansion. Consequently, the volume expansion of the secondary battery containing this artificial graphite during cycling is significantly reduced. Smaller volume expansion during cycling helps maintain a higher volumetric energy density; lower volume expansion also reduces the internal stress of the battery cell, reducing deformation caused by internal stress and effectively improving the safety performance of the secondary battery. Therefore, the artificial graphite involved in this application can improve the safety performance and energy density of the secondary battery. Furthermore, the low volume expansion of the secondary battery can maintain an internal structure suitable for electrolyte wetting during cycling, allowing the electrolyte to fully wet the cell, increasing lithium-ion transport channels, and thus improving the cycle performance of the secondary battery. Simultaneously, lower electrode expansion also helps avoid the risk of short circuits in the cell, thereby improving the safety performance of the secondary battery. The electrical device of this application includes the secondary battery provided in this application, and therefore has at least the same advantages as the secondary battery.
[0026] In the method for preparing artificial graphite provided in this application, after the graphitization step, the graphitized particles are mechanically treated using a mechanical fusion machine. This removes the sharp edges of the blocky particles, resulting in more rounded surfaces of the final artificial graphite particles. When this artificial graphite is used as the negative electrode active material for a secondary battery, the bonding force between particles can be significantly improved, thereby significantly reducing electrode expansion. This results in a secondary battery with low volume expansion during cycling and an electrical device incorporating the secondary battery. Attached Figure Description
[0027] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0028] Figure 1 This is a schematic diagram of a secondary battery provided in an embodiment of this application.
[0029] Figure 2 This is a schematic diagram of a battery module provided in an embodiment of this application.
[0030] Figure 3 This is a schematic diagram of a battery pack provided in an embodiment of this application.
[0031] Figure 4 yes Figure 3 The exploded diagram.
[0032] Figure 5 This is a schematic diagram of an electrical device provided in an embodiment of this application.
[0033] Figures 6a-6c The images shown are SEM (scanning electron microscope) images of artificial graphite provided in Examples 1, 2, and 3 of this application, respectively.
[0034] The reference numerals in the attached figures are explained as follows:
[0035] 1. Battery pack;
[0036] 2. Upper box;
[0037] 3. Lower box;
[0038] 4. Battery module;
[0039] 5. Secondary battery. Detailed Implementation
[0040] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the artificial graphite and its preparation method, as well as secondary batteries and electrical devices of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0041] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0042] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0043] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0044] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0045] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0046] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0047] In the description of this article, it should be noted that, unless otherwise stated, "above" and "below" include the number itself, and "several" in "one or several" means two or more.
[0048] Electrical energy, as an economical, practical, clean, and easily controlled and converted form of energy, is increasingly being used in various electrical devices. Rechargeable batteries, due to their advantages such as high energy density, portability, lack of memory effect, and environmental friendliness, have become a preferred power source for these devices. However, during cycling, the negative electrode of a rechargeable battery expands in volume, leading to increased internal stress and potentially causing battery failure. This also limits the improvement of energy density, thus affecting battery lifespan and safety performance. Therefore, reducing the volume expansion of rechargeable batteries during cycling has become a key focus in the field of rechargeable battery technology.
[0049] Through extensive research, the inventors have observed that when artificial graphite including secondary particles satisfies the following conditions: the compacted density of artificial graphite powder under a pressure of 2t (in g / cm³) 3 The volume distribution particle size D of the artificial graphite vWhen the ratio A (in μm) is ≥0.5, the bonding force between artificial graphite particles, which are used as the active material of the negative electrode, can be significantly improved. This can significantly reduce the volume expansion of the secondary battery containing the artificial graphite during cycling. At the same time, this is also conducive to maintaining a high energy density of the secondary battery. This can improve the service life and safety performance of the secondary battery, as well as the battery module, battery pack and electrical device including the secondary battery.
[0050] Artificial graphite
[0051] A first aspect of this application provides an artificial graphite. The artificial graphite comprises secondary particles and satisfies: A ≥ 0.5, where A is the compacted density of the artificial graphite powder under 2t pressure and the volume distribution particle size D of the artificial graphite. v The ratio of 1.
[0052] The inventors discovered that when the compaction density of artificial graphite powder under a pressure of 2t is related to the volume distribution particle size D of the artificial graphite... v When the ratio A ≥ 0.5, the bonding force between the artificial graphite particles used as the negative electrode is significantly improved, thereby significantly reducing the cyclic expansion of the negative electrode and thus significantly reducing the volume expansion of the secondary battery containing this artificial graphite during cycling. The smaller volume increase of the secondary battery during cycling is beneficial for maintaining a high energy density. In particular, the low cyclic expansion of the secondary battery can maintain an internal structure suitable for electrolyte wetting during cycling, allowing the electrolyte to fully wet the cell, thereby improving the cycle life of the secondary battery. Simultaneously, the lower cyclic expansion of the secondary battery also reduces the internal stress of the cell, minimizing the deformation caused by internal stress, and effectively improving the safety performance of the secondary battery. The safety performance and service life of battery modules, battery packs, and electrical devices using this secondary battery are therefore improved.
[0053] In some embodiments, artificial graphite may satisfy: 0.50≤A≤1.40, for example 0.60≤A≤1.40, 0.70≤A≤1.30, 0.80≤A≤1.20, 0.50≤A≤1.30, 0.60≤A≤1.30, 0.70≤A≤1.00, etc.
[0054] In some embodiments, artificial graphite can be secondary particles.
[0055] In some embodiments, the compacted density of artificial graphite powder under a pressure of 2t can be 1.60 g / cm³. 3 -1.95g / cm 3 1.70 g / cm³ is an optional value. 3 -1.95g / cm 3 1.75g / cm3 -1.90g / cm 3 For example, 1.70 g / cm³ 3 1.80g / cm 3 1.90g / cm 3 1.95g / cm 3 1.70g / cm 3 -1.90g / cm 3 1.75g / cm 3 -1.95g / cm 3 1.80g / cm 3 -1.95g / cm 3 1.80g / cm 3 -1.90g / cm 3 When the compaction density of artificial graphite powder is within a suitable range, the compaction density of the negative electrode sheet can be increased, thereby further improving the energy density of the secondary battery.
[0056] In some embodiments, the volume distribution particle size D of artificial graphite v The thickness can be 1.5μm-3.5μm, optionally 1.8μm-3.2μm, and further optionally 2.0μm-3.2μm, such as 1.6μm-3.4μm, 1.7μm-3.3μm, 1.9μm-3.1μm, 2.0μm-3.0μm, 2.3μm-2.8μm, 2.5μm-3.5μm, etc. The appropriate D of artificial graphite... v 1. It is suitable to make it have a more rounded surface, which is beneficial to improve the bonding force between particles when used as a negative electrode active material, thereby effectively maintaining the contact between particles, reducing the increase of electrode thickness, reducing electrode cyclic expansion, which is not only beneficial to reduce the volume expansion of secondary battery during cyclic expansion, but also beneficial to improve the energy density of secondary battery.
[0057] In some embodiments, the volume distribution particle size D of artificial graphite v 50 can be 10.0μm-20.0μm, and can be selected from 12.0μm-18.0μm, such as 10.0μm-18.0μm, 14.0μm-16.0μm, 14.0μm-18.0μm, etc. Appropriate D of artificial graphite v 50 is suitable for achieving high ion and electron transport performance while reducing side reactions of the electrolyte at the negative electrode. It possesses appropriate D... v The 50% concentration of artificial graphite also helps to improve its own powder compaction density. Using this artificial graphite can make the electrode sheet have a higher compaction density, thereby improving the energy density of the secondary battery.
[0058] In some embodiments, the specific capacity of the artificial graphite is 350 mAh / g or higher, optionally 352 mAh / g or higher. The higher the specific capacity of the artificial graphite, the higher the energy density of the secondary battery containing it. The artificial graphite provided in this application has both low cycle expansion and high specific capacity. The combined effect of these two factors enables the secondary battery provided in this application to have both low cycle expansion characteristics and high energy density characteristics.
[0059] [Preparation methods for artificial graphite]
[0060] In a second aspect, this application provides a method for preparing artificial graphite, which can prepare any of the aforementioned artificial graphite.
[0061] This application provides a method for preparing artificial graphite, which includes the following steps:
[0062] S1: The raw materials are crushed, graded, and shaped to obtain the precursor;
[0063] S2: Granulate the precursor obtained in step S1 to obtain intermediate 1;
[0064] S3: The intermediate 1 obtained in step S2 is graphitized at a temperature of 2700℃-3200℃ to obtain intermediate 2;
[0065] S4: The intermediate 2 obtained in step S3 is mechanically processed in a mechanical fusion machine to obtain artificial graphite;
[0066] The artificial graphite comprises secondary particles and satisfies: A ≥ 0.5, where A is the compacted density of the artificial graphite powder under 2t pressure and the volume distribution particle size D of the artificial graphite. v The ratio of 1.
[0067] In some implementations, during mechanical processing, the rotation speed of the mechanical fusion machine can be 600 rpm-1400 rpm, optionally 800 rpm-1200 rpm, such as 600 rpm-1300 rpm, 600 rpm-1200 rpm, 700 rpm-1400 rpm, 800 rpm-1400 rpm, 800 rpm-1300 rpm, 900 rpm-1200 rpm, etc. When mechanically processing the intermediate 2 obtained in step S3, an appropriate rotation speed of the mechanical fusion machine can ensure that the desired particle size D is obtained. v 1 (can be 1.5μm-3.5μm, optionally 1.8μm-3.2μm, further optionally 2.0μm-3.2μm) of artificial graphite, thereby obtaining artificial graphite with the desired rounded surface.
[0068] In some implementations, the mechanical processing time can be 5-30 minutes, or 5-25 minutes, such as 10-30 minutes, 5-27 minutes, 5-26 minutes, 10-20 minutes, or 5-15 minutes. In mechanical processing, a suitable processing time can ensure that the desired particle size D is obtained. v 1 (can be 1.5μm-3.5μm, optionally 1.8μm-3.2μm, further optionally 2.0μm-3.2μm) of artificial graphite, thereby obtaining artificial graphite with the desired rounded surface.
[0069] In some implementations, the raw materials may include one or more of the following: petroleum coke, calcined petroleum coke, needle coke, calcined needle coke, pitch coke, and metallurgical coke; optionally, the raw materials may include one or more of the following: petroleum coke, needle coke, and calcined needle coke.
[0070] In some embodiments, the raw material can be crushed in step S1 using equipment and methods known in the art, such as air jet mills, mechanical mills, or roller mills. The crushing process often produces a large number of excessively small particles, and sometimes excessively large particles as well. Therefore, after crushing, grading can be performed as needed to remove excessively small and excessively large particles from the crushed powder. Grading treatment yields a particulate product with a better particle size distribution. v The particle size can be 8.0-13.5 μm to facilitate subsequent shaping and / or granulation processes. Grading can be performed using equipment and methods known in the art, such as grading sieves, gravity classifiers, centrifugal classifiers, etc.
[0071] In some embodiments, in step S1, the particle product obtained after grading can be shaped using equipment (e.g., a shaping machine or other shaping equipment) and methods known in the art, such as grinding the edges of the particle product obtained after grading, which facilitates subsequent operations and makes the product obtained after shaping have higher stability.
[0072] In some embodiments, step S1 may further include removing fine powder after shaping. Fine powder removal can be performed using equipment and methods known in the art, such as classifying sieves, gravity classifiers, centrifugal classifiers, etc.
[0073] In some embodiments, the precursor obtained in step S1 is granulated in step S2 to aggregate the independently dispersed primary particles into secondary particles. During the granulation process, a binder may be used. Optionally, the amount of binder may be 2%-15% of the weight of the precursor used for granulation in step S2, such as 2%-12%, 4%-12%, 5%-15%, 6%-10%, etc.; optionally, the binder may include one or more of coal tar, asphalt, epoxy resin, and phenolic resin.
[0074] In step S2, granulation can be performed using equipment known in the art, such as a granulator. A granulator typically includes a stirred reactor and a module for temperature control of the reactor. Furthermore, by adjusting process conditions such as stirring speed, heating rate, granulation temperature, and cooling rate during the granulation process, the D of the granulated product (i.e., intermediate 1) can be controlled. v 50 is 14.5-24.0 μm. Optionally, in this application, the stirring speed during granulation is 800 r / min-1500 r / min, the heating rate is 8-15℃ / min, the granulation temperature is 400℃-650℃, and the granulation time is 6-10 hours.
[0075] In some embodiments, the intermediate 1 obtained in step S2 is graphitized in step S3 to obtain intermediate 2. In some embodiments, the temperature for graphitization in step S3 can be 2700℃-3200℃, such as 2700℃-3100℃, 3000℃-3200℃, 2800℃-3100℃, etc.
[0076] In some embodiments, during the mechanical processing in step S4, the rotation speed of the mechanical fusion machine can be 600 rpm-1400 rpm, optionally 800 rpm-1200 rpm, such as 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1100 rpm, 1400 rpm, 600 rpm-1200 rpm, 700 rpm-1200 rpm, 900 rpm-1100 rpm, etc. The processing time of the mechanical processing can be 5 min-30 min, optionally 5 min-25 min, such as 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 5 min-25 min, 5 min-20 min, 5 min-15 min, 10 min-20 min, etc. Suitable ranges of mechanical fusion machine rotation speed and processing time can not only remove the sharp edges of blocky particles, making the final artificial graphite particles more rounded and helping to improve the bonding force between particles, but also improve the volume distribution particle size D of the obtained artificial graphite. v1. The compacted density of the powder, within the range of 1.5μm-3.5μm and under a pressure of 2t, is 1.60 g / cm³. 3 -1.95g / cm 3 Within this range, it helps to obtain artificial graphite that satisfies A≥0.5 (where A is the compacted density of artificial graphite powder under 2t pressure (in g / cm³)). 3 The volume distribution and particle size D of artificial graphite v The ratio of 1 (in μm) can significantly reduce the cyclic expansion of the negative electrode containing the artificial graphite and the volume expansion of the secondary battery containing the artificial graphite during cycling, thus helping to obtain a secondary battery with both high volumetric energy density and low volumetric cyclic expansion. When the rotation speed and mechanical processing time of the mechanical fusion machine exceed the above range, excessively high rotation speed and excessively long time will lead to an increase in surface defects of the material, and the capacity of the secondary battery containing the artificial graphite will decay too quickly during cycling. When the rotation speed and mechanical processing time of the mechanical fusion machine are below the above range, excessively low rotation speed and excessively short time will result in insufficient removal of particle edges, no improvement in the bonding force between particles, and an insignificant effect in reducing expansion.
[0077] D of artificial graphite v 1. D v 50 can be determined using a laser particle size analyzer (such as Malvern Master Size 3000) in accordance with standard GB / T 19077.1-2016.
[0078] Among them, D v 1. D v The physical definition of 50 is as follows:
[0079] D v 1: Particles accounting for 1% of the total volume have a diameter smaller than this value.
[0080] D v 50: 50% of the total volume particles have a diameter greater than this value, and another 50% of the total volume particles have a diameter smaller than this value. (D) v 50 indicates the median particle size of the powder.
[0081] The compaction density of artificial graphite powder can be tested using methods known in the art. For example, it can be tested using an electronic pressure testing machine (such as UTM7305) according to GB / T24533-2009: a certain amount of powder is placed on a special compaction mold, different pressures are set, and the thickness of the powder under different pressures can be read on the equipment, and the compaction density under different pressures can be calculated.
[0082] Rechargeable batteries
[0083] This application provides a secondary battery comprising any type of artificial graphite provided in the first aspect of the present invention or any type of artificial graphite prepared by the method provided in the second aspect of the present invention.
[0084] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.
[0085] [Negative electrode plate]
[0086] The negative electrode includes a negative current collector and a negative electrode film disposed on at least one surface of the negative current collector. As an example, the negative current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative current collector.
[0087] The negative electrode current collector can be made of a material with good conductivity and mechanical strength, serving both as a conductor and a current collector. In some embodiments, the negative electrode current collector can be made of copper foil.
[0088] The negative electrode film includes a negative electrode active material, which includes any of the artificial graphite provided in the first aspect of this application. This significantly reduces the volume expansion of the negative electrode sheet comprising artificial graphite during cycling. Lower volume expansion not only helps the secondary battery maintain a high volumetric energy density but also helps reduce the internal stress within the battery cell, minimizing deformation under internal stress and effectively improving the safety performance of the secondary battery.
[0089] In some embodiments, the step of preparing a negative electrode sheet using any one or more artificial graphite materials of this application may include: dispersing a negative electrode active material including any one or more artificial graphite materials of this application, a binder, and optional thickeners and conductive agents in a solvent, the solvent being deionized water, to form a uniform negative electrode slurry; coating the negative electrode slurry onto a negative electrode current collector, and obtaining a negative electrode sheet after processes such as drying and cold pressing.
[0090] In some embodiments, the negative electrode sheet may optionally include other negative electrode active materials that can be used as the negative electrode of a secondary battery. Other negative electrode active materials may be one or more of other graphite materials (such as other artificial graphite, natural graphite), mesophase microcarbon spheres (MCMB), hard carbon, soft carbon, silicon-based materials, and tin-based materials.
[0091] In some embodiments, the adhesive may be selected from one or more of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0092] In some embodiments, the thickener may be sodium carboxymethyl cellulose (CMC-Na).
[0093] In some embodiments, the conductive agent used for the negative electrode sheet may be selected from one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0094] [Positive electrode plate]
[0095] The positive electrode includes a positive current collector and a positive electrode film disposed on at least one surface of the positive current collector and comprising a positive active material. As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0096] The positive current collector can be made of a material with good conductivity and mechanical strength. In some embodiments, the positive current collector can be aluminum foil.
[0097] This application does not impose specific restrictions on the type of positive electrode active material. Materials known in the art that can be used as positive electrodes for secondary batteries can be used. Those skilled in the art can select according to actual needs.
[0098] In some embodiments, the secondary battery may be a lithium-ion secondary battery. The positive electrode active material may be selected from lithium transition metal oxides and their modified materials, wherein the modified material may be a lithium transition metal oxide that has undergone doping modification and / or coating modification. For example, the lithium transition metal oxide may be selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium phosphates with an olivine structure.
[0099] As an example, the positive electrode active material of a secondary battery can be selected from LiCoO2, LiNiO2, LiMnO2, LiMn2O4, and LiNi. 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 One or more of O2, LiFePO4 (LFP), and LiMnPO4.
[0100] In some embodiments, the positive electrode membrane may optionally include an adhesive. There is no specific limitation on the type of adhesive, and those skilled in the art can select one according to actual needs. As an example, the adhesive used for the positive electrode membrane may include one or more of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).
[0101] In some embodiments, the positive electrode membrane may optionally include a conductive agent. There is no specific limitation on the type of conductive agent, and those skilled in the art can select it according to actual needs. As an example, the conductive agent used for the positive electrode membrane may include one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0102] [Electrolytes]
[0103] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.
[0104] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0105] In some embodiments, the electrolyte salt may be selected from one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalate borate), LiBOB (lithium dioxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorodioxalate phosphate), and LiTFOP (lithium tetrafluorooxalate phosphate).
[0106] In some embodiments, the solvent may be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0107] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, additives that improve battery low-temperature performance, etc.
[0108] [Isolation membrane]
[0109] Secondary batteries using electrolytes, and some secondary batteries using solid electrolytes, also include a separator. The separator is positioned between the positive and negative electrodes to provide isolation. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected. In some embodiments, the separator material can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.
[0110] [Outer Packaging]
[0111] In some embodiments, the secondary battery may include an outer packaging for encapsulating a positive electrode, a negative electrode, and an electrolyte. As an example, the positive electrode, negative electrode, and separator may be stacked or wound to form a stacked or wound battery cell, with the cell encapsulated within the outer packaging; the electrolyte may be a liquid electrolyte that wets the cell. The number of cells in the secondary battery may be one or more, adjustable as needed.
[0112] In some embodiments, the outer packaging of the secondary battery can be a soft pack, such as a pouch. The soft pack can be made of plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS). The outer packaging of the secondary battery can also be a hard shell, such as an aluminum shell.
[0113] In some embodiments, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly by a winding process or a stacking process.
[0114] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. Figure 1 This is an example of a square-structured secondary battery 5.
[0115] The secondary batteries provided by this invention can be assembled into battery modules. The number of secondary batteries contained in a battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0116] Figure 2 This is battery module 4, used as an example. (See reference...) Figure 2 In battery module 4, multiple secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple secondary batteries 5 can be fixed in place using fasteners.
[0117] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of secondary batteries 5 are received.
[0118] In this invention, battery modules assembled from secondary batteries can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0119] Figure 3 and Figure 4 This is battery pack 1 as an example. (See reference...) Figure 3 and Figure 4 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0120] Electrical appliances
[0121] This application also provides an electrical device, which includes a secondary battery provided by this application, the secondary battery providing power to the electrical device. The electrical device may be, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0122] The electrical device can be equipped with a secondary battery, battery module, or battery pack according to its usage requirements.
[0123] Figure 5 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.
[0124] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use rechargeable batteries as their power source.
[0125] Example
[0126] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0127] [Performance Testing]
[0128] (1) Specific capacity test of artificial graphite
[0129] The prepared artificial graphite, conductive agent Super P, thickener (CMC-Na), and binder (SBR) were mixed with deionized water in a mass ratio of 94.5:1.5:1.5:2.5 to form a slurry. The prepared slurry was coated onto a copper foil current collector and dried in an oven for later use. A lithium metal sheet was used as the counter electrode. A polyethylene (PE) film was used as the separator. Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1. LiPF6 was then uniformly dissolved in the above solution to obtain an electrolyte with a concentration of 1 mol / L. The above components were assembled into a CR2430 coin cell in an argon-protected glove box.
[0130] After the obtained coin cells were left to stand for 12 hours, they were discharged at a constant current of 0.05C to 0.005V, left to stand for 10 minutes, and then discharged at a constant current of 50μA to 0.005V. After leaving to stand for 10 minutes, they were discharged at a constant current of 10μA to 0.005V. Then, they were charged at a constant current of 0.1C to 2V, and the charging capacity was recorded. The ratio of the charging capacity to the mass of the artificial graphite is the specific capacity of the prepared artificial graphite.
[0131] (2) Cyclic expansion rate test of negative electrode sheet
[0132] The thickness of the cold-pressed negative electrode sheet is denoted as H0. The cold-pressed negative electrode sheet, along with the positive electrode sheet, separator, and electrolyte, is used to construct a secondary battery. At 25°C, the secondary battery is subjected to 1C / 1C cycles at 100% DOD (100% depth of discharge, i.e., full charge followed by full discharge) using a Newway charge / discharge machine. The discharge capacity of the first cycle (i.e., the initial capacity) is denoted as 100%. The cycle is stopped when the cycle capacity retention rate reaches 80% of the initial capacity. The secondary battery is then charged to 100% SOC (State of Charge), disassembled, and the thickness of the corresponding negative electrode sheet is measured and denoted as H1. The cycle expansion rate of the negative electrode sheet is then: (H1 / H0-1)×100%.
[0133] (3) Cyclic capacity retention
[0134] A charge-discharge test was conducted on a lithium-ion battery at 25℃. One charge-discharge cycle was as follows: constant current charging at 1C to 4.3V, then constant voltage charging at 4.3V to 0.05C, resting for 5 minutes, and then constant current discharging at 1C to 2.8V. The battery capacity at this point was recorded as C1. This constitutes one charge-discharge cycle. This process was repeated 1200 times, and the battery capacity C1200 was recorded. Therefore, the cycle capacity retention rate = C1200 / C1 × 100%.
[0135] (4) Cohesive force test of negative electrode sheet
[0136] Apply double-sided tape to both sides of a 2cm wide stainless steel plate. Evenly attach the electrode to be tested onto the tape, ensuring it is of uniform length and width. Evenly apply copper foil tape to the electrode surface (ensuring a smooth, wrinkle-free surface after application), leaving a small section of copper foil tape attached to a piece of paper (the copper foil and paper should be in a straight line). Set the tensile testing machine parameters and place the electrode vertically in the center of the machine's slot, ensuring it is perfectly aligned vertically. Click "Start Test" on the computer to obtain the cohesive force data.
[0137] Example 1
[0138] Preparation of artificial graphite
[0139] S1: Needle-shaped raw coke is fed into a jaw crusher via a vibrating feeder for coarse crushing. The qualified material is then fed into a mechanical mill for fine crushing, grading, and shaping to obtain D. v 50 is a precursor with a diameter of 11 μm;
[0140] S2: Add the precursor obtained in step S1 to the reactor, and add 10% (D) of binder bitumen relative to the weight of the precursor used for granulation. vGranulation was performed using 50 granules (5μm-8μm) at a stirring speed of 1200 r / min. The temperature was then increased to 560℃ at a rate of 10℃ / min at room temperature, and held at that temperature for 8 hours until the granules reached D. v 50 is 18μm, thus intermediate 1 is obtained;
[0141] S3: Add intermediate 1 obtained in step S2 into a graphitization furnace, heat to 3000℃ for graphitization treatment, and sieve with a 200-mesh sieve to obtain intermediate 2;
[0142] S4: The intermediate 2 obtained in step S3 is placed in a mechanical fusion machine for mechanical processing. The mechanical fusion machine rotates at 900 rpm, and the mechanical processing time is 15 minutes, to obtain D. v 50 is 14μm, D v The compacted density of a powder with a particle size of 2 μm under a pressure of 2 t is 1.8 g / cm³. 3 The artificial graphite with a specific capacity of 357 mAh / g has the following specific performance parameters, as shown in Table 1. SEM images of the artificial graphite prepared in Example 1 are shown below. Figure 6a As shown.
[0143] Preparation of negative electrode sheet
[0144] The artificial graphite, conductive agent (Super P), binder (SBR), and thickener (CMC-Na) prepared above were thoroughly mixed in an appropriate amount of deionized water at a mass ratio of 96.2:0.8:1.8:1.2 to form a uniform negative electrode slurry. The negative electrode slurry was then coated onto the surface of a copper foil current collector, and after drying and cold pressing, a negative electrode sheet was obtained. The compacted density of the negative electrode sheet was 1.65 g / cm³. 3 Its surface density is 11.4 mg / cm³. 2 The cohesive force test results, cycle expansion rate results, and cycle capacity retention rate results of the negative electrode sheet are shown in Table 2 below.
[0145] Preparation of positive electrode sheet
[0146] LiNi, the positive electrode active material 0.5 Co 0.2 Mn 0.3 O2 (NCM523), conductive agent (Super P), and binder PVDF are thoroughly mixed in an appropriate amount of NMP at a weight ratio of 96.2:2.7:1.1 to form a uniform positive electrode slurry. The positive electrode slurry is then coated onto the surface of the positive electrode current collector aluminum foil, dried, and cold-pressed to obtain the positive electrode sheet. The compacted density of the positive electrode sheet is 3.45 g / cm³. 3 Its surface density is 18.8 mg / cm³. 2 .
[0147] Preparation of electrolyte
[0148] Ethyl carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and then LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte with a concentration of 1 mol / L.
[0149] Separating membrane
[0150] Polyethylene (PE) film is used.
[0151] Preparation of secondary batteries
[0152] The positive electrode, separator, and negative electrode are stacked in sequence and wound to obtain a battery cell. The battery cell is then placed in an outer packaging, and the electrolyte mentioned above is added. After processes such as encapsulation, settling, formation, and aging, a secondary battery is obtained. The outer packaging is a hard shell with a length * width * height of 148mm * 28.5mm * 97.5mm.
[0153] Example 2-14
[0154] The preparation methods of Examples 2-6 are similar to those of Example 1, except that the raw materials for preparing artificial graphite are adjusted. The process parameters of each example and the test results of the physical parameters of the prepared artificial graphite are shown in Table 1 below. The cohesive force test results, cycle expansion rate results of the negative electrode sheet containing the artificial graphite, and the cycle capacity retention rate results of the secondary battery containing the negative electrode sheet are shown in Table 2 below.
[0155] Specifically, in Example 2, the raw material for preparing artificial graphite was calcined petroleum coke; in Example 3, the raw material for preparing artificial graphite was raw petroleum coke (without using a binder); in Example 4, the raw material for preparing artificial graphite was calcined needle coke; in Example 5, the raw material for preparing artificial graphite was pitch coke; and in Example 6, the raw material for preparing artificial graphite was metallurgical coke. Figure 6b and Figure 6c SEM images of the artificial graphite prepared in Examples 2 and 3, respectively.
[0156] The preparation methods of Examples 7-9 are similar to those of Example 1, except that the amount of binder used in the granulation process of preparing artificial graphite is adjusted. The process parameters of each example and the test results of the physical parameters of the prepared artificial graphite are shown in Table 1 below. The cohesive force test results, cycle expansion rate results of the negative electrode sheet containing the artificial graphite, and the cycle capacity retention rate results of the secondary battery containing the negative electrode sheet are shown in Table 2 below.
[0157] Specifically, in Example 7, the amount of binder bitumen used was 15% of the weight of the precursor used for granulation in step S2; in Example 8, the amount of binder bitumen used was 8% of the weight of the precursor used for granulation in step S2; and in Example 9, the amount of binder bitumen used was 5% of the weight of the precursor used for granulation in step S2.
[0158] The preparation methods of Examples 10-11 are similar to those of Example 1, except that the graphitization temperature of the artificial graphite is adjusted. The process parameters of each example and the test results of the physical parameters of the prepared artificial graphite are shown in Table 1 below. The cohesive force test results, cycle expansion rate results of the negative electrode sheet containing the artificial graphite, and the cycle capacity retention rate results of the secondary battery containing the negative electrode sheet are shown in Table 2 below.
[0159] The preparation methods of Examples 12-14 are similar to those of Example 1, except that the degree of mechanical fusion treatment in the preparation of artificial graphite is adjusted. The process parameters of each example and the test results of the physical parameters of the prepared artificial graphite are shown in Table 1 below. The cohesive force test results, cycle expansion rate results of the negative electrode sheet containing the artificial graphite, and the cycle capacity retention rate results of the secondary battery containing the negative electrode sheet are shown in Table 2 below.
[0160] Comparative Examples 1-12
[0161] Comparative Examples 1-6 were prepared using methods similar to those of Examples 1-6, except that no mechanical fusion treatment was performed after graphitization in step S3. The process parameters of each comparative example and the test results of the physical parameters of the prepared artificial graphite are shown in Table 1 below. The cohesive force test results, cycle expansion rate results, and cycle capacity retention rate results of the negative electrode sheet containing the artificial graphite are shown in Table 2 below.
[0162] Comparative Examples 7-10 were prepared using methods similar to those in Example 1, except that the degree of mechanical fusion treatment in step S4 was adjusted. The process parameters of each comparative example and the test results of the physical parameters of the prepared artificial graphite are shown in Table 1 below. The cohesive force test results, cycle expansion rate results, and cycle capacity retention rate results of the negative electrode sheet containing the artificial graphite are shown in Table 2 below.
[0163] Comparative Examples 11-12 are prepared using methods similar to those in Example 1, except that the mechanical processing method in step S4 is adjusted. Specifically, in Comparative Example 11, a high-speed airflow impact granulator (temperature 600°C, processing time 8 hours) is used to mechanically crush and spheroidize the intermediate 2 obtained in step S3, and then sieve it to obtain D. v50 consists of spherical artificial graphite particles with a diameter of 10μm-15μm; in Comparative Example 12, intermediate 2 obtained in step S3 was mechanically crushed and spheroidized using an airflow vortex mill (power 0.7MPa), and then sieved to obtain D. v 50 consists of spherical artificial graphite particles with a diameter of 10μm-15μm. The process parameters of each comparative example and the test results of the physical parameters of the prepared artificial graphite are shown in Table 1 below. The cohesive force test results, cycle expansion rate results, and cycle capacity retention rate results of the negative electrode sheet containing this artificial graphite are shown in Table 2 below.
[0164] Table 1: Test results of process and physical parameters of Examples 1-14 and Comparative Examples 1-12
[0165]
[0166]
[0167]
[0168] Table 2: Performance test results of Examples 1-14 and Comparative Examples 1-12
[0169]
[0170]
[0171] As can be seen from the comparison of Examples 1-14 and Comparative Examples 1-12 shown in Tables 1 and 2 above, after graphitization treatment, appropriate mechanical fusion treatment of intermediate 2 can make the prepared artificial graphite satisfy A of 0.5 or higher (e.g., 0.50≤A≤1.40, optionally 0.70≤A≤1.30, and further optionally 0.70≤A≤1.00, where A is the compaction density of artificial graphite powder under 2t pressure and its volume distribution particle size D). v The ratio of 1 to 1 can significantly improve the cohesive force of the negative electrode containing the artificial graphite, and has a significant effect on reducing the cycle expansion rate of the electrode. At the same time, it can maintain a high specific capacity of the artificial graphite. This has a significant effect on reducing the volume expansion of the secondary battery containing the artificial graphite during the cycle and improving the energy density and cycle capacity retention rate of the secondary battery. Therefore, it can effectively improve the service life and safety performance of the secondary battery.
[0172] In Comparative Examples 1-6, there was no mechanical fusion treatment step after the graphitization process. As a result, the negative electrode sheet produced had a higher cycle expansion rate and lower cohesion. This is not conducive to reducing the volume expansion of the secondary battery containing the negative electrode sheet during cycling and is also not conducive to improving the energy density of the secondary battery.
[0173] In Comparative Examples 7-8, the mechanical fusion processing time was either too long or too short. In Comparative Example 7, the excessively long processing time reduced the cycle capacity retention rate of the secondary battery. In Comparative Example 8, the excessively short mechanical fusion processing time resulted in a negative electrode and secondary battery with performance comparable to those obtained in Comparative Examples 1-6 without mechanical processing. In Comparative Examples 9-10, the mechanical fusion machine's rotation speed was either too low or too high. In Comparative Example 9, the excessively low rotation speed failed to achieve the purpose of mechanical processing, resulting in a negative electrode and secondary battery with performance comparable to those obtained in Comparative Examples 1-6 without mechanical processing. In Comparative Example 10, the excessively high rotation speed combined with the excessively short mechanical processing time could reduce the cycle expansion rate of the negative electrode to some extent, but the excessively high rotation speed was detrimental to improving the cycle capacity retention rate of the secondary battery.
[0174] Comparative Examples 11-12 used a high-speed airflow impact granulator and an airflow vortex pulverizer to mechanically crush and spheroidize the intermediate 2 obtained in step S3. Although spheroidized artificial graphite was obtained in both cases, the results showed that using the above two mechanical processing devices was not conducive to improving the cohesion of the negative electrode sheet, and the effect on reducing the cyclic expansion rate of the negative electrode sheet was not obvious. Furthermore, it was difficult to control the degree of mechanical processing of the airflow vortex pulverizer, resulting in low stability.
[0175] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A type of artificial graphite, characterized in that, The artificial graphite comprises secondary particles and satisfies: 0.70≤A≤1.40; Wherein, A represents the compacted density of the artificial graphite powder under a pressure of 2t and the particle size D of the artificial graphite volume distribution. v The ratio of 1, where the unit of the compacted density of the powder is g / cm³. 3 The volume distribution particle size D v The unit of 1 is μm; The volume distribution particle size D of the artificial graphite v 1 represents 1.5 μm - 3.5 μm.
2. The artificial graphite according to claim 1, characterized in that, The artificial graphite satisfies: 0.70≤A≤1.
30.
3. The artificial graphite according to claim 1, characterized in that, The artificial graphite is made of secondary particles.
4. The artificial graphite according to claim 1, characterized in that, The compacted density of the artificial graphite powder under a pressure of 2 t is 1.60 g / cm³. 3 -1.95 g / cm 3 .
5. The artificial graphite according to claim 4, characterized in that, The compacted density of the artificial graphite powder under a pressure of 2 t is 1.70 g / cm³. 3 -1.90 g / cm 3 .
6. The artificial graphite according to claim 1, characterized in that, The volume distribution particle size D of the artificial graphite v 1 is 1.8 μm - 3.2 μm.
7. The artificial graphite according to claim 1, characterized in that, The volume distribution particle size D of the artificial graphite v 1 represents 2.0 μm - 3.2 μm.
8. The artificial graphite according to claim 1, characterized in that, The volume distribution particle size D of the artificial graphite v 50 represents 10.0 μm - 20.0 μm.
9. The artificial graphite according to claim 8, characterized in that, The volume distribution particle size D of the artificial graphite v 50 is 12.0 μm - 18.0 μm.
10. The artificial graphite according to claim 1, characterized in that, The specific capacity of the artificial graphite is above 350 mAh / g.
11. The artificial graphite according to claim 10, characterized in that, The specific capacity of the artificial graphite is above 352 mAh / g.
12. A method for preparing artificial graphite, characterized in that, Includes the following steps: S1: The raw materials are crushed, graded, and shaped to obtain the precursor; S2: Granulate the precursor obtained in step S1 to obtain intermediate 1; S3: The intermediate 1 obtained in step S2 is graphitized at a temperature of 2700℃-3200℃ to obtain intermediate 2; S4: The intermediate 2 obtained in step S3 is mechanically processed in a mechanical fusion machine to obtain artificial graphite; The artificial graphite comprises secondary particles and satisfies: 0.70 ≤ A ≤ 1.40, where A is the compacted density of the artificial graphite powder under 2 t pressure and the volume distribution particle size D of the artificial graphite. v The ratio of 1, where the unit of the compacted density of the powder is g / cm³. 3 The volume distribution particle size D v The unit of 1 is μm; the volume distribution particle size D of the artificial graphite v 1 represents 1.5 μm - 3.5 μm.
13. The preparation method according to claim 12, characterized in that, During mechanical processing, the rotational speed of the mechanical fusion machine is 600 rpm - 1400 rpm.
14. The preparation method according to claim 13, characterized in that, During mechanical processing, the rotational speed of the mechanical fusion machine is 800 rpm - 1200 rpm.
15. The preparation method according to claim 12, characterized in that, The processing time for the mechanical treatment is 5 min to 30 min.
16. The preparation method according to claim 15, characterized in that, The processing time for the mechanical treatment is 5 min to 25 min.
17. The preparation method according to claim 12, characterized in that, A binder is added during the granulation process, and the weight of the added binder is 5%-15% of the weight of the precursor used for granulation in step S2.
18. The preparation method according to claim 17, characterized in that, The binder includes one or more of coal tar, asphalt, epoxy resin, and phenolic resin.
19. The preparation method according to claim 12, characterized in that, The raw materials include one or more of the following: petroleum coke, calcined petroleum coke, needle coke, calcined needle coke, pitch coke, and metallurgical coke.
20. The preparation method according to claim 19, characterized in that, The raw materials include one or more of petroleum coke, needle coke, and calcined needle coke.
21. A secondary battery, characterized in that, It includes a negative electrode sheet, the negative electrode sheet comprising a negative electrode active material, the negative electrode active material comprising artificial graphite according to any one of claims 1-11 or comprising artificial graphite prepared by the method according to any one of claims 12-20.
22. An electrical appliance, characterized in that, Includes the secondary battery as described in claim 21.
Citation Information
Patent Citations
Cell anode material and preparation method thereof
CN104810508A
Artificial graphite, secondary battery, preparation method, and device
CN113207316A